2009
DOI: 10.1002/pbc.21955
|View full text |Cite
|
Sign up to set email alerts
|

KIR–HLA receptor‐ligand mismatch associated with a graft‐versus‐tumor effect in haploidentical stem cell transplantation for pediatric metastatic solid tumors

Abstract: Killer immunoglobulin-like receptors (KIRs) on natural killer cells (NKs) recognize groups of human leukocyte antigen (HLA) class I alleles. Cells without an inhibitory HLA ligand may trigger NK activation. Reduced risk of relapse has been reported in malignant hematologic diseases after haploidentical transplantation when HLA ligands against the inhibitory KIRs present in the donor were absent in the recipient. We performed haploidentical transplant in three children with refractory solid tumors. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 20 publications
(23 reference statements)
3
52
0
1
Order By: Relevance
“…We choose to use rabbit antithymocyte globulin in the conditioning regimen to maximize the NK cell GVT effect. Indeed, neuroblastoma cells express low levels or no HLA class I potentially making them excellent targets for NK cells, 9,33 and we have shown that rabbit anti-thymocyte globulin enhances IFN-production by NK cells. 34 However, our data suggest that the profound T-cell depletion induced by rabbit anti-thymocyte globulin should also be taken into account, and its use in future trials is questionable.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We choose to use rabbit antithymocyte globulin in the conditioning regimen to maximize the NK cell GVT effect. Indeed, neuroblastoma cells express low levels or no HLA class I potentially making them excellent targets for NK cells, 9,33 and we have shown that rabbit anti-thymocyte globulin enhances IFN-production by NK cells. 34 However, our data suggest that the profound T-cell depletion induced by rabbit anti-thymocyte globulin should also be taken into account, and its use in future trials is questionable.…”
Section: Discussionmentioning
confidence: 91%
“…2,3 Given a higher rate of TRM with allogeneic hematopoietic SCT and the occurrence of GVHD, autologous is the preferred therapeutic option for those in need of hematopoietic SCT: only 25 allogeneic transplantations were therefore performed for neuroblastoma in Europe in 2006. [4][5][6][7][8][9] However, progress has been made in allogeneic transplantation both from a better understanding of immunogenicity and decreased transplant toxicity. First, it has been shown that the GVT effect of allogeneic transplantation may be enhanced by several therapeutic modalities: rapid immunosuppression withdrawal, donor lymphocyte infusion, 10,11 natural killer (NK) cell alloreactivity, 9,12 minor histocompatiblity Ag targeting.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In pediatric solid tumors, this has also been observed in a limited number of patients. 8,14 Moreover, several pediatric solid tumors are characterized by reduced expression of HLA class I qualifying them valid targets for NK cell lysis. 15,16 Here, we present two patients with relapsed EWS after autologous hematopoietic stem cell transplantation (HSCT) who have undergone an allogeneic haploidentical HSCT as rescue treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of NK cells after haploidentical transplantation is well described by missing-self, KIRmismatched or activation of NKG2D/NKG2DL. 10,11,22,23 We have shown higher NK-cell numbers in recipients of haplo-SCT compared with recipients of parent-F1 transplant (Figure 4). Haploidentical NK cells have shown in vitro/in vivo anti-tumor activity to solid tumors and can be used as an adoptive therapy in the clinic.…”
Section: Discussionmentioning
confidence: 82%
“…Non-myeloablative haplo-HSCT was reported to induce anti-tumor activity in one patient with advanced RCC after successful engraftment, but the patient eventually developed progression of the disease 1 year after transplant. 9 Pé rez-Martínez et al 10,11 reported that three patients with pediatric metastatic solid tumors were transplanted with mobilized T-cell-depleted (TCD) peripheral stem cells from haploidentical donors. One patient with mismatched killer immunglobulin like receptors (KIR)-HLA achieved CR and was alive 21 months after transplant at time of the report, suggesting that KIR-HLA receptor-ligand mismatch could induce GVT activity after haplo-SCT.…”
Section: Introductionmentioning
confidence: 99%